2022
DOI: 10.1186/s40793-022-00454-w
|View full text |Cite
|
Sign up to set email alerts
|

Legacy effects of fumigation on soil bacterial and fungal communities and their response to metam sodium application

Abstract: Background Soil microorganisms are integral to maintaining soil health and crop productivity, but fumigation used to suppress soilborne diseases may affect soil microbiota. Currently, little is known about the legacy effects of soil fumigation on soil microbial communities and their response to fumigation at the production scale. Here, 16S rRNA gene and internal transcribed spacer amplicon sequencing was used to characterize the bacterial and fungal communities in soils from intensively managed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 117 publications
0
1
0
Order By: Relevance
“…Our findings highlight the significant influence of both the treatments (biostimulant and fumigation) and the time periods on specific ASVs that were positively or negatively affected in the treated soils. Our results are consistent with those reported by Li et al (64), who found that chloropicrin fumigation exposure enriched the abundance of Pseudarthrobacter, Sphingomonas, Pseudomonas, Domibacillus, Nocardioides, and Paenibacillus at the genus level, many of which have known beneficial functions in promoting crop growth, antagonizing plant pathogens, and interacting with soil nitrogen cycling.…”
Section: Treatments Effects On Soil Bacterial Community Compositionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings highlight the significant influence of both the treatments (biostimulant and fumigation) and the time periods on specific ASVs that were positively or negatively affected in the treated soils. Our results are consistent with those reported by Li et al (64), who found that chloropicrin fumigation exposure enriched the abundance of Pseudarthrobacter, Sphingomonas, Pseudomonas, Domibacillus, Nocardioides, and Paenibacillus at the genus level, many of which have known beneficial functions in promoting crop growth, antagonizing plant pathogens, and interacting with soil nitrogen cycling.…”
Section: Treatments Effects On Soil Bacterial Community Compositionsupporting
confidence: 93%
“…Previous studies have found that in bacterial community, Proteobacteria, Actinobacteriota and Firmicutes were more abundant while Acidobacteriota were less abundant in soils exposed to chloropicrin (17, 25, 65). Also, our findings are consistent with previous studies that reported that chloropicrin fumigation altered bacterial phyla relative abundance and sustained changes of bacterial community compared to the effects of other non-fumigated treatments (22,64).…”
Section: Treatments Effects On Soil Bacterial Community Compositionsupporting
confidence: 92%
“…The interaction circle diagram of species composition was drawn by Krona [43]. Alphadiversity indexes, including the Chao 1, Shannon, and Simpson, were calculated in QIIME 2 [44], and the statistical significance was calculated using the two-tailed, unpaired Student's t-test, followed by the Benjamini, Krieger and Yekutieli procedure for false discovery rate (FDR) correction. We used the Non-Metric Multi-Dimensional Scaling (NMDS) method to evaluate the difference in beta diversity between treatments [45].…”
Section: Discussionmentioning
confidence: 99%
“…Soil fumigation can control and kill root-knot nematodes, soil-borne pathogens, and weeds [43]. Wang et al [44] reported that the inhibition rate of Phytophthora spp.…”
Section: Discussionmentioning
confidence: 99%